Nilai-Nilai Pendidikan Agama Hindu Dalam Upacara Ngapon Tapakan Panawa Sanga di Pura Luhur Pucak Padang Dawa - Kadek Dwi Sentana Putra; I Made Sukma Muniksu (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
The implementation of this study aims to examine the values of Hindu religious education contained in a ceremony, especially the Ngapon Tapakan Panawa Sanga ceremony located at Pura Luhur Pucak Padang Dawa. The island of Bali, which is an island with a majority Hindu population, has a cultural diversity that reflects Hinduism itself. Balinese people in their lives always balance between humans and nature, humans and humans and humans and God. On this occasion the researcher examined the values of Hindu religious education at the Ngapon Tapakan Panawa Sanga ceremony at Luhur Pucak Padang Dawa Temple, Bangli Village, Baturiti District, Tabanan Regency. This procession was carried out over a long period of time, this can be seen from the hermitage itself. Indirectly, the community and the next generation maintain and preserve traditions passed down from their ancestors. The values of Hindu Religious Education studied are the values contained in the Ngapon Tapakan Panawa Sanga ceremony at Luhur Pucak Padang Temple, Dawa Bangli Village, Baturiti District, Tabanan Regency, including: Values of Tattwa Education (philosophy), Values of Ethical Education, Values of Ceremonial Education (rituals), and the Value of Aesthetic Education.